Respuestas

2012-04-28T06:59:07+02:00

1.-

 

(4sen3x-1)dx = 4sen3x dx - dx 

 

4sen3x dx = 4sen3x dx           u=3x

                   = (4/3)senu du     du=3dx       dx=du/3

                   =(4/3)(-cosu)

                   =(4/3)(-cos3x)

 

dx=x

 

entonces la respuesta seria

 

(4sen3x-1)dx = -\frac{4}{3}cos (3x) - x +c

 

2.-

(2eu+6/u+Ln 2u+6)du = 2eu du + (6/u) du + ln2u du + 6 du

 

= 2eudu + 6(1/u) du + ln2u du + 6 du

 

= eu²+6lnu+(1/2)(xlnx-x)+6u

 

ESPERO TE SEA DE AYUDA, SALUDOS